Experiencial profesional adquirida en “Baker Hughes Oil Field Operation sucursal del Peru S.A. – Upstream Chemical, línea de tratamiento químico en operaciones de producción de petróleo” - Vela Meléndez, Miguel Angel (2025)
The Report describes the professional experience acquired at Baker Hughes Company, specifically in the area of treatment of fluids produced in oilfield, presents the equipment used for the treatment of oil and reinjection water, shows the problems present in the different stages of the process and also explains the solution through the application of chemical products such as demulsifiers, clarifiers, scale inhibitors, corrosion inhibitors and indicates the method standards applied for quality control of production fluids in oil fields. Within the experience acquired, it makes a reference to the projects participated, such as the “Zero Discharge” project and details a practical methodology for the evaluation of chemical products at laboratory stage, highlighting as a recommendation the constant application of this methodology for continuous improvement.